Α-Lipoic acid prevents senescence, cell cycle arrest, and inflammatory cues in fibroblasts by inhibiting oxidative stress. (March 2019) - Baeeri, Maryam; Bahadar, Haji; Rahimifard, Mahban; Navaei-Nigjeh, Mona; Khorasani, Reza; Rezvanfar, Mohammad Amin; Gholami, Mahdi; Abdollahi, Mohammad
Graphical abstract: Abstract: Senescence is a process characterized by an irreversible growth arrest in cells and induced by oxidative stress. In the current study, anti-aging potential of a well-known antioxidant, α-lipoic acid (α-LA), in rat embryonic fibroblast (REF) cells was assessed. In this regard, oxidative stress, inflammation, and apoptosis pathways were investigated on REF cells exposed to H2 O2 as a senescence inducer and α-LA as a protective compound. In cells treated with α-LA and H2 O2, level of β-galactosidase, as an aging marker, and oxidative stress biomarkers, were significantly lower than those exposed to H2 O2 only. Furthermore, flow cytometry assay showed that α-LA caused a significant reduction in the number of apoptotic cells via the caspase-dependent pathway. In addition, it could neutralize the inflammatory effects of H2 O2 and attenuated the concentration of inflammatory cytokines. In comparison to H2 O2 group, a significant increase in G0/G1 arrest was observed during cell cycle analysis in cells exposed to H2 O2 and α-LA. The results of this study show that α-LA has beneficial effects on H2 O2 -induced cellular senescence. α-LA works by attenuating the reactive oxygen species, subsiding inflammation, and affecting cell division.